Storytelling before bed, is it still effective? Mendongeng Sebelum Tidur, Masihkah Efektif Dilakukan? - Bawono, Yudho; Wibowo, Wasis Purwo; Listiyana, Ar Liza; Muarif, Samsul; Aditya, Puji Restu (Procedia of Social Sciences and Humanities, 2024)
Bedtime storytelling is an oral tradition that has been passed down for generations. Many previous studies have found the benefits of storytelling, which is usually given to children at bedtime. Some of them are: (1) Fostering a proactive attitude; (2) Strengthening the relationship between parents and children; (3) Increasing knowledge; (4) Training concentration; (5) Increasing vocabulary; (6) Fostering interest in reading; (7) Triggering children's critical thinking; (8) Stimulating children's imagination, fantasy, and creativity; and (9) Providing lessons without seeming patronizing. However, behind the various benefits of bedtime storytelling, with the development of technology, especially media using the internet, the question arises, is bedtime storytelling still effective today? The purpose of this study is to find out whether storytelling before bed is effective for children. The research was conducted by distributing Questionnaires of Children's Activities Listening to Fairy Tales in the form of google forms. The results showed 139 respondents (90.3%) answeredyes, 13 respondents (8.4%) answered neutral, and 2 respondents (1.3%) answered no. Based on the results, it can be said that storytelling before bedtime is still effective. Based on the results of the study, it can be said that storytelling (before bed) is still effective, especially to improve children's language skills.